Susceptibility-weighted imaging in post-treatment evaluation in the early stage in patients with acute ischemic stroke. Issue 1 (January 2019) - Liang, Jia; Gao, Peiyi; Lin, Yan; Song, Ligang; Qin, Haiqiang; Sui, Binbin
Objective: This study aimed to investigate the association between abnormal signs on susceptibility-weighted imaging (SWI) and post-treatment outcome in the early stage in patients with acute ischemic stroke. Methods: Thirty-seven patients with middle cerebral artery territory infarction were recruited. Baseline and 24-hour follow-up magnetic resonance imaging was performed. Pre- and 24-hour post-treatment clinical conditions were assessed with the National Institutes of Health Stroke Scale (NIHSS) score. Prominent vessel sign (PVS) on SWI and infarcted areas on diffusion-weighted imaging (DWI) were assessed using the Alberta Stroke Program Early CT (ASPECT) score system. Susceptibility vessel sign (SVS) was evaluated and recorded. The associations between image abnormalities and clinical scores were analyzed. Results: PVS was found in 35 patients and SVS in seven patients. The extent of PVS was significantly correlated with the post-treatment DWI ASPECT score (r = 0.79), but not with the post-treatment NIHSS score or the post−pre NIHSS difference score. The presence of SVS was significantly correlated with the post-treatment NIHSS score (r = 0.41). Conclusion: PVS might be a useful predictor of early imaging prognosis and infarct growth in patients with acute ischemic stroke. SVS is related to a poor early outcome and could be useful for assessing stroke.